Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21614/chirurgia.115.1.39
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Systemic Inflammation Markers in the Survival of Patients with Complicated Colorectal Cancer, Operated in Emergency

Abstract: Introducere: Răspunsul inflamator joacă un rol critic în carcinogeneză. Există scoruri recente bazate pe răspunsul inflamator sistemic, cum ar fi raportul neutrofile/limfocite (NLR), raportul trombocite/limfocite (PLR), raportul limfocite/monocite (LMR), despre care s-a arătat că au valoare prognostică la pacienţii cu cancer. Aceste scoruri permit identificarea pacienţilor care vor avea un răspuns slab la tratament şi o supravieţuire de scurtă durată. Scopul acestui studio este de a evalua rolul prognostic al … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…We showed that the increased preoperative value of NLR was a negative prognostic factor for longterm survival, as found by other authors [23][24][25][26]. In a single study conducted in 2018 at the University of Leeds in the UK, the authors reported that elevated NLR values were associated with a high risk of death in univariate but not multivariate analysis [27].…”
Section: Discussionsupporting
confidence: 85%
“…We showed that the increased preoperative value of NLR was a negative prognostic factor for longterm survival, as found by other authors [23][24][25][26]. In a single study conducted in 2018 at the University of Leeds in the UK, the authors reported that elevated NLR values were associated with a high risk of death in univariate but not multivariate analysis [27].…”
Section: Discussionsupporting
confidence: 85%
“…PLR measurements can provide important diagnostic and prognostic information for patients with resectable gastric cancer. Georgiana et al [ 8 ] retrospectively analyzed 391 patients who were admitted to the hospital and who underwent surgery for complicated CRC. In the multivariate regression analysis, the increase in the PLR resulted in an increased risk of death (hazard ratio (HR) = 1.024; 95% CI = 1.019.1.029; P value = 0.000000), and the PLR was thus considered an independent risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have shown that the systemic inflammatory response is related to tumor progression. The platelet-to-lymphocyte ratio (PLR) and C-reactive protein (CRP), which are two inflammation-related biomarkers, have been confirmed to be prognostic indicators in early gastric cancer, gastrointestinal cancers, and CRC [6][7][8]. However, to our knowledge, no studies have reported the association among PLR, CRP, and the histological type of colorectal polyps.…”
Section: Introductionmentioning
confidence: 99%
“…Georgiana et al [8] retrospectively analyzed 391 patients who were admitted to the hospital and who underwent surgery for complicated CRC. In the multivariate regression analysis, the increase in the PLR resulted in an increased risk of death (hazard ratio (HR) = 1.024; 95% CI = 1.019.1.029; P value = 0.000000), and the PLR was thus considered an independent risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have shown that the systemic in ammatory response is related to tumor progression. The platelet-to-lymphocyte ratio (PLR) and C-reactive protein (CRP), which are two in ammation-related biomarkers, have been con rmed to be prognostic indicators in early gastric cancer, gastrointestinal cancers, and CRC [6][7][8]. However, to our knowledge, no studies have reported the association among PLR, CRP, and the histological type of colorectal polyps.…”
Section: Introductionmentioning
confidence: 99%